Helicity Amplitudes for Generic Multibody Particle Decays Featuring Multiple Decay Chains - Daniele Marangotto (Advances in High Energy Physics)
We present the general expression of helicity amplitudes for generic multibody particle decays characterised by multiple decay chains. This is achieved by addressing for the first time the issue of the matching of the final particle spin states among different decay chains in full generality for generic multibody decays, proposing a method able to match the exact definition of spin states relative to the decaying particle ones. We stress the importance of our result by showing that one of the matching methods used in the literature is incorrect, leading to amplitude models violating rotational invariance. The results presented are therefore relevant for performing numerous amplitude analyses, notably those searching for exotic structures like pentaquarks.